Pengaruh Debt to Equity Ratio dan Debt to Asset Ratio Terhadap Profitabilitas Perusahaan Sub Sektorkosmetik dan Barang Keperluan Rumah Tangga yang Terdaftar di Bursa Efek Indonesia Periode 2020-2024 - Fitri Angraeni; La Ode Turi; Nichen . (CV. ITTC INDONESIA, 2025)
The increasingly competitive nature of the cosmetics and household goods industry demands companies to manage their capital structure effectively in order to enhance profitability. However, empirical findings regarding the influence of capital structure on firm performance remain inconsistent, creating the need for further investigation. This study aims to analyze the relationship between capital structure—proxied by the Debt to Equity Ratio (DER) and Debt to Asset Ratio (DAR)—and profitability, measured using Return on Assets (ROA), in cosmetic and household goods sub-sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. This research employs a quantitative approach using the Partial Least Square (PLS) method, with data processed through SmartPLS version 4. The results show that DER has a positive and significant effect on ROA, with an original sample value of 0.859 and a P-value of 0.000 (P < 0.05). Likewise, DAR also has a positive and significant effect on ROA, with an original sample value of 0.182 and a P-value of 0.000 (P < 0.05). These findings indicate that increasing the proportion of debt within the capital structure can enhance firm profitability. Overall, the results support the trade-off theory, which asserts that the optimal use of debt can strengthen firm performance and improve profitability.